Detection of a Left Superior Vena Cava during a Pacemaker Implantation in Cotonou - A. Sonou; M. Hounkponou; L. Codjo; P. M. Adjagba; C. Houehanou; H. Dohou; S. Assani; Y. Tchabi; M. Houenassi (Case Reports in Cardiology)
Persistent left superior vena cava (LSVC) is a rare congenital anomaly. Its prevalence in the general population is 0.1 to 0.5%. LSVC is 5 times rarer when accompanied by an absence of the right superior vena cava (RSVC). We present the case of a 54-year-old man who carries a persistent LSVC without RSVC. Clinically, this patient presented a regular bradycardia at 40 per minute associated with a heart failure syndrome. The electrocardiogram diagnosed a complete atrioventricular block and transthoracic echocardiography showed dilated left heart cavities and a left ventricular ejection fraction of 50%. During the procedure of pacemaker implantation, the probe followed an unusual LSVC-coronary sinus-right atrium path and it was not easy to pass through the tricuspid orifice. We propose a review of the literature on this subject, focusing on the clinical implications of this malformation in cardiac stimulation and in other areas of cardiology.